Analisis Kebijakan Penetapan Harga Jual Rumah pada Perumahan PT. Nasaliansyah Developer Jambi - Laila Farhat; Marnas Marnas (Universitas Batanghari, 2020)
This research was conducted to analyze the pricing policy set by the housing developer PT. Nasaliansyah Jambi, which aims to determine the selling price of sales proceeds. This research is a qualitative descriptive study that describes the determination of the selling price of the house by the developer of PT. Nasaliansyah Jambi, with survey methods and field research. The results of the study prove that by increasing the number of orders and the amount of income received by the housing developer PT. Nasaliansyah Jambi in 2015 amounted to 90 units until 2018 to a total of 420 housing units sold. Price affects the choice of type of house purchased by consumers. The selling price of a house is influenced by the price of the materials that will be used to build a house. Likewise, promotional costs affect sales volume, the greater the promotion costs, the higher the sales volume of houses in PT. Nasaliansyah Jambi.